Optimization of SIM Services by Traffic Unit Satpas Madiun City Police for Increasing Public Trust - Mutmaina, Nurindry Erika (Advances in Police Science Research Journal, 2024)
The Driver's License (SIM) service is an implementation of the duties and responsibilities of the SIM Administration Unit (SATPAS) of the Madiun City Police Traffic Unit in carrying out the registration and identification functions. Good or bad SIM services have an impact on the level of public trust in the Police institution, especially in the traffic sector. The purpose of writing this final project is to describe and describe the organizational resources of SATPAS Traffic Unit of Madiun City Police, analyze the application of management functions, and identify innovations of SATPAS Traffic Unit of Madiun City Police in optimizing SIM services to increase public trust. This research is a qualitative type with a field research approach. Data were obtained using observation techniques, in-depth interviews, and document studies. The theories and concepts used are management function theory, management elements theory, competency theory, innovation diffusion theory, optimization concept, public service concept, SIM concept, SATPAS concept, Traffic Unit concept, public trust concept and Drive&Roll concept. The results showed that the organizational resources of SATPAS Traffic Unit of Polres Madiun Kota, the application of management functions, and the innovation of SATPAS Traffic Unit of Polres Madiun Kota in SIM services were not fully adequate and in accordance with the relevant theories, concepts, or police regulations, causing SIM services by SATPAS Traffic Unit of Polres Madiun Kota in increasing public trust not yet optimal. Therefore, Kanit Regident as the subject of this final project needs to take problem-solving steps.